2018
DOI: 10.1021/acs.langmuir.7b03678
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization with Carboxylic Acids by Photochemical Microcontact Printing and Tetrazole Chemistry

Abstract: In this paper, we show that carboxylic acid-functionalized molecules can be patterned by photochemical microcontact printing on tetrazole-terminated self-assembled monolayers. Upon irradiation, tetrazoles eliminate nitrogen to form highly reactive nitrile imines, which can be ligated with several different nucleophiles, carboxylic acids being the most reactive. As a proof of concept, we immobilized trifluoroacetic acid to monitor the reaction with X-ray photoelectron spectroscopy. Moreover, we also immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Recent studies have showed that tetrazoles react with different kinds of nucleophiles, upon photolysis, in a biological system. Therefore, we performed negative control experiments to prove the importance of the tetrazole-ene photoclick reaction in living systems (Figure S15a). The cell lysates containing CTz-SO 3 exhibited very weak fluorescence under normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have showed that tetrazoles react with different kinds of nucleophiles, upon photolysis, in a biological system. Therefore, we performed negative control experiments to prove the importance of the tetrazole-ene photoclick reaction in living systems (Figure S15a). The cell lysates containing CTz-SO 3 exhibited very weak fluorescence under normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The N1ss pectra of the irradiated parts of both surfaces differ significantly fromt he respective dark parts. The signals in the non-irradiated sections at 402.7 and 400.2 eV are assigned to the surface bound tetrazole species [44,62] and are similar for both S-Pt and S-Pd,a sw ell as in the case of the free ligand surface S-LP2 ( Figure S74). In contrast,t he irradiated areas are dominated by the nitrogen atoms of ther espective metal complexesc entred at 400.2 eV,w hich are attributed to C=NÀPt and C=NÀPd, respectively.A dditionally,t he N1ss pectra shows af urther weak peak at 398.9 eV belonging to the nitrogen in the aromatic rings of LP2,w hereast he tetrazole-as-signed peak at 402.7 eV disappeared.…”
Section: Surfaceattachment Through Preloaded Metallopolymersmentioning
confidence: 94%
“…μCP as a kind of soft lithography possessing many advantages, including high resolution, very short reaction times, simple large-area patterning, low cost, and so forth. [40][41][42] Certainly, it can help to solve the disadvantages encountered in microfabrication, which is the basic technology used in making all microelectronic systems, such as high cost, complex facilities and technologies for high-energy radiation needed, and limitations to extremely flat silicon substrates. μCP allows the patterned transfer of a molecular ink onto a surface using an elastomeric stamp.…”
Section: Microcontact Printingmentioning
confidence: 99%